1997
DOI: 10.1161/01.atv.17.9.1716
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transfer Inhibitor Protein Activity Deficiency in Normolipidemic Uremic Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: We previously demonstrated that lipid transfer inhibitor protein (LTIP) is a potent modifier of lipid transfer protein (LTP) function in vitro. Based on these studies, we proposed that LTIP activity is an important determinant of lipoprotein size and composition, which leads to a stimulation of reverse cholesterol transport. To further evaluate this hypothesis, we have studied a normolipidemic, uremic patient population undergoing continuous ambulatory peritoneal dialysis (CAPD) that is deficient in LTIP activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…CETP plus near-physiological levels of LTIP replicated the preferential transfer of CE from HDL typically seen in plasma, whereas CETP alone could not. These findings are consistent with our recent observations in an LTIP activitydeficient patient population, 39 where CETP-mediated CE fluxes from LDL and HDL to VLDL were equivalent when the lipoproteins are compared on the basis of their CE content. We suggest that the apparent preferential transfer of HDL lipids by CETP in plasma 38,39,53,54 reflects the activity of LTIP, not the lipoprotein selectivity of CETP.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…CETP plus near-physiological levels of LTIP replicated the preferential transfer of CE from HDL typically seen in plasma, whereas CETP alone could not. These findings are consistent with our recent observations in an LTIP activitydeficient patient population, 39 where CETP-mediated CE fluxes from LDL and HDL to VLDL were equivalent when the lipoproteins are compared on the basis of their CE content. We suggest that the apparent preferential transfer of HDL lipids by CETP in plasma 38,39,53,54 reflects the activity of LTIP, not the lipoprotein selectivity of CETP.…”
Section: Discussionsupporting
confidence: 93%
“…This lack of lipoprotein specificity by CETP is not an in vitro artifact due to lipoprotein isolation since no preference for HDL is seen in whole plasma from patients deficient in LTIP activity. 39 We have recently observed that increased negative charge on lipoproteins results in increased stable CETP-lipoprotein binding, but that the effects of these modification on CETP activity are highly dependent on the nature of the derivatization itself (Morton R.E. and Greene D.J., unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations